ANALISIS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA HOTEL TIARA GUMAWANG BELITANG OKU TIMUR - Imroah, Jamilatul; Yansahrita, Yansahrita (Jurnal Trisna Riset, 2025)
A hotel is a company engaged in the service sector. These services include 24-hour room service, restaurants, complete facilities, seminar and meeting places, wifi area, fitness lab and laundry services. No matter how good the physical condition of a hotel building is if it is not supported by maximum service, customers will still not be satisfied. Based on this, a study was conducted to determine the cause of the decline in the number of guests staying at the Tiara Hotel. This study aims to determine customer satisfaction with the quality of service provided by the Tiara Hotel Gumawang OKU Timur. Data collection techniques used include library research and field research through observation, questionnaires, interviews and documentation. From the calculation of the correlation coefficient with the t-count result is 0.584. After the hypothesis test was carried out, the t-count value was 20035 while the table value was 1.970, thus the t-count value was greater than the t-table value, so it can reject the null hypothesis (HO) and accept the alternative hypothesis (Ha). Based on the results of the analysis, it can be concluded that the correlation between the influence of service placement on customer satisfaction at the Tiara Gumawang OKU Timur Hotel obtained by the Y figure is 0.584 after being consulted with the conservation standard, it turns out to be 0.400 0.599 which is included in the strong correlation. Hypothesis testing proves that service quality has a significant effect on customer satisfaction. Therefore, it is recommended that hotel management pay more attention to employee performance and conduct periodic evaluations to improve service quality.